Analisis Faktor-faktor yang Mempengaruhi Perilaku Ibu Hamil dalam Pemanfaatan Pelayanan Antenatal Care (K4) di Wilayah Kerja Puskesmas Tarus - Welhelmina Daril Tassi; Masrida Sinaga; Rut Rosina Riwu (Media Kesehatan Masyarakat, 2021)
The Antenatal Care (ANC) service's success is seen from the coverage of K4, which is the number of pregnant women who have obtained ANC services with a minimum of four times the recommended schedule in each trimester during pregnancy. The achievement of K4 coverage at Tarus Health Center in the last three years has not reached the national MSS target (95%), which is 71,86% (2017), 77,63% (2018), and 65,48% (2019). This study aimed to determine the factors associated with the ANC (K4) visit in pregnant women in the Tarus Health Centre's working area. The type of research is an analytical survey using a cross-sectional design with a sample of 75 people and conducted in August-September 2020. The statistical test used is the Chi-Square test. The results showed that the related variables were the knowledge level (p=0,000), maternal attitude (p=0,006), service accessibility (p=0,035), and exposure to media information (p=0,000). Unrelated were husband support (p=0,291) and attitude of health workers (p=0.870). Health Centers should give regular counselling, supported by printed media, electronic media, and other media information that can increase pregnant women's participation in using ANC (K4) services. The public is expected to be involved.